PKM Use Of Information Systems To Increase Learning Motivation Using Microsoft Sway In Students Of Nuurul Muttaqiin Vocational School Cisurupan Garut - Umamah, Ai; Bariyah, Siti Husnul; Faujiah, Siti (Indonesian Journal of Community Empowerment (IJCE), 2024)
This community service with the title Utilization of information systems to increase learning motivation using Microsoft SWAY for students of SMK Nuurul Muttaqiin Cisurupan Garut. PKM is carried out at SMK Nuurul Muttaqiin Cisurupan Garut. The objectives include: 1) to increase learning motivation, 2) utilization of application-based information technology, the methods used are lectures, cooperation, and mentoring. In this service, the results that have been achieved have received a good response to the implementation of PKM, which is indicated by the interest in learning to use the sway application. Pengabdian kepada masyarakat ini dengan judul Pemanfaatan sistem informasi untuk meningkatkan motivasi Belajar Menggunakan Microsoft SWAY pada Siswa/Siswi SMK Nuurul Muttaqiin Cisurupan Garut. PKM di laksanakan di SMK Nuurul Muttaqiin Cisurupan Garut. Tujuannya antara lain : 1) untuk meningkatkan motivasi belajar, 2) pemanfaatan teknologi informasi berbasis aplikasi, metode yang di gunakan ceramah, kerjasama, dan pendampingan. Dalam pengabdian ini hasil yang telah di capai mendapat respon baik terhadap pelaksanaan PKM, yang di tujukan dengan ketertarikan untuk belajar menggunakan aplikasi sway.